No evidence for intervention-associated DNA methylation changes in monocytes of patients with posttraumatic stress disorder - Hummel, Elisabeth; Elgizouli, Magdeldin; Sicorello, Maurizio; Leitão, Elsa; Beygo, Jasmin; Schröder, Christopher; Zeschnigk, Michael; Müller, Svenja; Herpertz, Stephan; Moser, Dirk; Kessler, Henrik; Horsthemke, Bernhard; et al. (Scientific reports, 2022)
DNA methylation patterns can be responsive to environmental influences. This observation has sparked interest in the potential for psychological interventions to influence epigenetic processes. Recent studies have observed correlations between DNA methylation changes and therapy outcome. However, most did not control for changes in cell composition. This study had two aims: first, we sought to replicate therapy-associated changes in DNA methylation of commonly assessed candidate genes in isolated monocytes from 60 female patients with post-traumatic stress disorder (PTSD). Our second, exploratory goal was to identify novel genomic regions with substantial pre-to-post intervention DNA methylation changes by performing whole-genome bisulfite sequencing (WGBS) in two patients with PTSD. Equivalence testing and Bayesian analyses provided evidence against physiologically meaningful intervention-associated DNA methylation changes in monocytes of PTSD patients in commonly investigated target genes (NR3C1, FKBP5, SLC6A4, OXTR). Furthermore, WGBS yielded only a limited set of candidate regions with suggestive evidence of differential DNA methylation pre- to post-therapy. These differential DNA methylation patterns did not prove replicable when investigated in the entire cohort. We conclude that there is no evidence for major, recurrent intervention-associated DNA methylation changes in the investigated genes in monocytes of patients with PTSD.
Gesehen am 18.01.2023